OVERVIEW OF EMPLOYMENT OF PRODUCTIVE ZAKAT IN THE SPECIALIZE OF THE ISTIRJA SENTENCE PHILOSOPHY FOR POVERTY REDUCTION IN INDONESIA - Nur Ika Mauliyah; Warga Baroka Sugiarto; Muhammad Korib Hamdani (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
In 2022 poverty in Indonesia will reach 26.37 million people. This requires attention in overcoming poverty before spreading to other sectors. Based on an Islamic economic point of view, the purpose of operational behavior of assets is not only to lead to personal interests but to benefit many people. The starting point of this research study is to embed the philosophy of istirja' in the management of productive zakat in Indonesia. The preparation of this scientific paper is based on the philosophy of istirja' sentences. This study uses a literature study with qualitative descriptive data analysis which emphasizes phenomena and the sharp instincts of the researcher. Basically, in an Islamic perspective, Allah SWT has sent down mercy for all mankind, but due to human activities many problems have been manifested that require the concept of istirja' to lead a life according to Islamic guidelines (Al-Qur'an). The results of the study show that the level of poverty can be minimized through the utilization of productive zakat potential in Indonesia. The concept of istirja' in the sense of returning or implementing it in accordance with Islamic teachings, the presence of productive zakat can essentially invite all Indonesian people to implement istirja' by forming a solution to the above. With the largest Muslim population in the world, the income of zakat funds increases annually to reach Rp. 327 Trillion in 2022.